Subjective and Objective Evaluation of the Effect of Blink Type on Tear-film Breakup Time and Its Estimation - Szczesna-Iskander, Dorota H.; Llorens Quintana, Clara (Optometry and vision science, 2020)
SIGNIFICANCEWhile evaluating the tear-film breakup time, a careful set of precise instructions should be given to the subjects regarding the blink type because it substantially impacts the assessment of tear-film surface quality. PURPOSEThe purpose of this study was to determine to what extent the type of blink affects the tear-film breakup time and its assessment using two types of videokeratoscopes and the fluorescein test. METHODSThirty-three volunteers were assessed considering two different types of blinksnatural (short) and forced (unnaturally prolonged). Objective noninvasive breakup time estimation was performed using Oculus Keratograph 5M and Medmont E300, both equipped with tear-film analysis modules, followed by the fluorescein test. In addition, while overviewing videokeratoscopy recordings, noninvasive breakup time was assessed subjectively by one experienced observer marking the first noticeable distortion in the Placido-disk pattern. Statistical analyses included two-way ANOVA and paired-sample t test. The agreement between blinking and measuring modalities was assessed using Bland-Altman plots. RESULTSForced blink significantly shortened the tear-film breakup time in all measuring modalities (two-way ANOVA, P = .003). The mean difference between breakup time after natural and forced blink was 3.2 (P = .002), 2.4 (P = .005), and 2.1 seconds (P = .002), for Keratograph 5M, E300, and fluorescein test, respectively. The group median of differences between objective and subjective noninvasive breakup time was less than 1 second with both videokeratoscopes. The objective noninvasive breakup time measured with Keratograph 5M was significantly longer than those with E300 and fluorescein test (both P < .001). No statistically significant difference was found between E300 objective assessment and fluorescein test (P = .19). CONCLUSIONSForced blinks affect the assessment of tear-film stability. Hence, attention should be given in instructing the subjects before tear-film breakup time evaluation irrespectively to the method of measurement.